Combined method of spectral estimation when receiving of superpermissions on frequency - V. A. Kakora; A. V. Grinkevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Evaluating of the power spectral density (SPM) of signal are usually performed through procedures using classical methods spectral analysis based on the discrete Fourier transform. This approach to spectral analysis is computationally efficient and provides acceptable results. However, in spite of these advantages, a classical method has a number of fundamental limitations. The most important of these is the limitation of the frequency resolution. For the solution of a problem of increase in the frequency resolution, in practice such methods as MUSIC, EV, Berg, MD assessment etc. In article presents classical methods of estimation power spectrum density, method the minimum error variance (MD estimate) and developed combined method.